QUIMISHOW: um game de misturas e métodos de separação - SOUZA, Fábio Pacheco de (2024)
A significant portion of contemporary society lives in a world deeply marked by the use of Information and Communication Technologies (ICT) in basic activities across various contexts of everyday life. On the other hand, there persists a reality characterized by a very low Human Development Index, as in Melgaço city, where access to these technologies is hindered. We understand that the school is an important instrument for social transformation and should be a place for access and encouragement to the creative use of ICT, thus needing to be an environment for the democratization of these technologies, contributing to learning and digital and social inclusion. We hope that the developed didactic resource can contribute to addressing social exclusion while enhancing the learning of the proposed knowledge objects. In order to provide opportunities and harness the communication potential of the ICT, this work involved the development of a Learning Object for teaching the knowledge objects of Mixtures and Separation of mixtures, in accordance with the new curricular standards brazilian, the Base Nacional Comum Curricular (BNCC). The Learning Object, named "Mixtures and Separation Methods," was graphically created using Microsoft PowerPoint tools for the Windows operating system. As a result, a didactic resource was obtained, for offline access, contributing to both the teaching and learning processes. It functions as a game for assessment, providing feedback on the concepts evaluated in each question, allowing for affirmation or correction of the concepts addressed.